AB0506 Longitudinal change of the titer of anti-mda5 antibody and association with prognosis in dermatomyositis with interstitial pneumonia. (23rd January 2014) - Nakashima, R.; Fujiwara, R.; Hosono, Y.; Imura, Y.; Yukawa, N.; Yoshifuji, H.; Ohmura, K.; Fujii, T.; Mimori, T.
Abstract : Background: Anti-MDA5 antibody is one of dermatomyositis-specific autoantibodies and its characteristic clinical meanings have been reported. It associates with clinically amyopathic dermatomyositis (CADM), hyperferritinemia, acute or subacute interstitial pneumonia (A/SIP) and poor prognosis especially in Asian patients. Recently, an ELISA system which can detect anti-MDA5 antibody was established and some reported that its titer seems to be associated with disease activity. However, it has not been yet clear how anti-MDA5 titer changes during long term or whether it associates with other clinical markers. Objectives: We followed anti-MDA5 titer closely and longitudinal clinical course. Methods: We prepared recombinant His-MDA5 protein (520a.a. of c-terminus) expressed in Eschericha coli . After confirming antigenic activity of the recombinant protein using immunoblotting, we made an ELISA system. Efficiency was confirmed using the sera from 31 Japanese DM patients (23 anti-MDA5-positive and 8 anti-MDA5 negative patients) and 25 healthy controls. The presence of Anti-MDA5 was confirmed by immunoprecipitation using 35 S-methionine-labeled HeLa cells. Sera from 14 anti-MDA5-positive patients were collected during disease course (range: 3-133 weeks). The titer at 0, 4, 8, 12 weeks of the disease course were compared. The association between the titer and several serum markers (ferritin, KL-6, IL-6 and M-CSF) were assessed. Results: The cut-off point was defined at 56.7 U on the basis of mean+4SD of healthy controls and both sensitivity and specificity of the ELISA were 100%. In anti-MDA5-positive patients, the antibody titer tended to be higher in the deceased (n=7) than in the alive (n=11) but there was no statistical significance (p=0.057). In the alive patients, the anti-MDA5 titer gradually decreased especially 8 weeks after the desease onset. After 11 weeks, the antibody titer decreased under the cut-off point in some patients and after 52 weeks, the titer went down to the mean level of the healthy control in 4 of 5 patients. There was no association between anti-MDA5 titer and serum ferritin or IL-6 levels before treatment but anti-MDA5 titer was correlated with serum ferritin in 3 of 6 patients at longitudinal study in each disease course. In one patient, KL-6 was also associated with the antibody titer. IL-6 and M-CSF were not associated with the titer during the disease course. Conclusions: The ELISA system for anti-MDA5 antibody is useful not only in diagnosis of DM but also in estimating prognosis and following disease activity during longitudinal time course in each patients. References: Sato S, et al. Mod Rheumatol 2012 May 29 [ahead of print] Gono T, et al. Rheumatology (Oxford). 2012 Sep;51(9):1563-70. Disclosure of Interest: None Declared